2007
DOI: 10.1186/1471-2407-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality trends in the Umbria region of Italy 1978–2004: a joinpoint regression analysis

Abstract: Background: The aim of the present paper was to analyse cancer mortality in the Umbria region, from 1978 to 2004. Mortality trends depend on a number of factors including exposures, health system interventions, and possibly artefact (e.g. classification change, variations of data completeness). Descriptive data on mortality only allow for generation of hypotheses to explain observed trends. Some clues on the respective role of possible mortality determinants may be found comparing mortality with incidence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In Europe, an overview of recent trends in mortality from neoplasias discussed there was a trend of increasing mortality from CRC for men and a reduction for women in Spain (14) . In Italy, researchers have shown a growing and statistically significant trend for men in the period 1978-2004 (15) . However, a study on mortality due to neoplasias carried out in European Union countries has observed a decrease in CRC mortality rates in both sexes (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, an overview of recent trends in mortality from neoplasias discussed there was a trend of increasing mortality from CRC for men and a reduction for women in Spain (14) . In Italy, researchers have shown a growing and statistically significant trend for men in the period 1978-2004 (15) . However, a study on mortality due to neoplasias carried out in European Union countries has observed a decrease in CRC mortality rates in both sexes (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study analyzed cancer mortality trends in the Umbria region from 1978 to 2004 (25) . The authors of that study observed non-significant trends in rates of CRC among women; however, they observed a constant increase in CRC rates among men (AAPC: 0.66; 95% CI: 0.28; 0.97).…”
Section: Discussionmentioning
confidence: 99%
“…Trend studies conducted worldwide have indicated a reduction in CRC mortality rates in most developed countries; however, in developing countries, this same trend has not been observed. Moreover, when the trends were analyzed by age and sex, different patterns were observed (1,2,24,25) . Reduction in mortality is one of the main objectives of interventions based on screening and treatment; therefore, studies can be useful in evaluating the policies and programs aimed at monitoring cancer care as well as the changes in outcomes due to population lifestyle, environmental risks and the effectiveness of the health care system (25) .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant decline in the incidence of gastric cancer in the world, especially European countries such as Spain and Italy, which is as the result of the substantial improvement of living conditions, it is passing an ascending trend in developing countries like Iran. Some of this incidence increase is related to improved cancer registry system [35] in the country, and perhaps some proportion of that is due to changes in risk factors of this cancer such as an increase in H. pylori infection [36][37][38][39][40][41]. Surveying the distribution of sex frequency of these patients in the study period shows that the incidence of this cancer is always higher in men.…”
Section: Discussionmentioning
confidence: 99%